Comprehensive analysis of expressed sequence tags from cultivated and wild radish (Raphanus spp.) - Shen, Di (BioMed Central, 2013)
BACKGROUND: Radish (Raphanus sativus L., 2n = 2× = 18) is an economically important vegetable crop worldwide. A large collection of radish expressed sequence tags (ESTs) has been generated but remains largely uncharacterized. RESULTS: In this study, approximately 315,000 ESTs derived from 22 Raphanus cDNA libraries from 18 different genotypes were analyzed, for the purpose of gene and marker discovery and to evaluate large-scale genome duplication and phylogenetic relationships among Raphanus spp. The ESTs were assembled into 85,083 unigenes, of which 90%, 65%, 89% and 89% had homologous sequences in the GenBank nr, SwissProt, TrEMBL and Arabidopsis protein databases, respectively. A total of 66,194 (78%) could be assigned at least one gene ontology (GO) term. Comparative analysis identified 5,595 gene families unique to radish that were significantly enriched with genes related to small molecule metabolism, as well as 12,899 specific to the Brassicaceae that were enriched with genes related to seed oil body biogenesis and responses to phytohormones. The analysis further indicated that the divergence of radish and Brassica rapa occurred approximately 8.9-14.9 million years ago (MYA), following a whole-genome duplication event (12.8-21.4 MYA) in their common ancestor. An additional whole-genome duplication event in radish occurred at 5.1-8.4 MYA, after its divergence from B. rapa. A total of 13,570 simple sequence repeats (SSRs) and 28,758 high-quality single nucleotide polymorphisms (SNPs) were also identified. Using a subset of SNPs, the phylogenetic relationships of eight different accessions of Raphanus was inferred. CONCLUSION: Comprehensive analysis of radish ESTs provided new insights into radish genome evolution and the phylogenetic relationships of different radish accessions. Moreover, the radish EST sequences and the associated SSR and SNP markers described in this study represent a valuable resource for radish functional genomics studies and breeding.